(untitled) (Computer systems and information technologies, 2022)
The purpose of the article is to analyze the course of socio-economic processes in Ukraine over the past eight years to make recommendations for improving their management policy. The complexity of the task was that the development of the studied processes is characterized by not one but several primary factors, the simultaneous analysis of which is not a trivial task. Among these factors are not only quantitative but also qualitative indicators, which makes our task poorly structured. In the analysis were used statistical and expert data that characterize socio-economic processes. This made it possible to consider the Russian military aggression against Ukraine and the situation with COVID-19 when making calculations. The use of qualitative information in the analysis makes it impossible to use methods of multidimensional statistics. To perform this task, it is proposed to use the theory of fuzzy logic and fuzzy sets. To describe the linguistic terms of fuzzy sets are used trapezoidal membership functions, the parameters of which are determined by experts. The constructed model of approximation of a nonlinear object with linguistic expressions allows finding the desired result faster and easier in comparison with the classical procedure of similar calculations. Using the considered approach in the article the tendencies of the development of social and economic processes in Ukraine from 2013 to 2020 are analyzed. The result of the calculations is the value of the generalized indicator, the value of which characterizes the level of development of socio-economic processes in the year. The obtained calculations showed that the value of this indicator was the highest in 2013. Over the next two years, this figure decreased and then began to grow slowly. The increase lasted until 2019, and in 2020 the value decreased again. However, in none of the years, 2014-2020 did the figure reach 2013. In our opinion, the main reason for the decrease in the level of development of socio-economic processes in 2014 and 2015 was Russia’s annexation of the Autonomous Republic of Crimea and the war in eastern Ukraine, and in 2020 - the effects of the COVID-19 pandemic.